2019
DOI: 10.1186/s12859-019-3040-x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating genetic networks into case-control association studies with high-dimensional DNA methylation data

Abstract: BackgroundIn human genetic association studies with high-dimensional gene expression data, it has been well known that statistical selection methods utilizing prior biological network knowledge such as genetic pathways and signaling pathways can outperform other methods that ignore genetic network structures in terms of true positive selection. In recent epigenetic research on case-control association studies, relatively many statistical methods have been proposed to identify cancer-related CpG sites and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Subsequently, Jiao et al proposed the functional epigenetic modules (FEM) method [ 67 ], which revealed HAND2 as a methylation hotspot in the endometrium and indicator of drug response in progesterone treatment [ 69 ]. Kim and Sun [ 71 ] showed that PPI networks are beneficial in network-regularized feature selection after dimension reduction. Li et al used principal component analysis for feature reduction and sparse canonical correlation analysis to infer edge weights for gene pairs.…”
Section: Network Medicine In the Clinical Setting Of Cancer Preventiomentioning
confidence: 99%
“…Subsequently, Jiao et al proposed the functional epigenetic modules (FEM) method [ 67 ], which revealed HAND2 as a methylation hotspot in the endometrium and indicator of drug response in progesterone treatment [ 69 ]. Kim and Sun [ 71 ] showed that PPI networks are beneficial in network-regularized feature selection after dimension reduction. Li et al used principal component analysis for feature reduction and sparse canonical correlation analysis to infer edge weights for gene pairs.…”
Section: Network Medicine In the Clinical Setting Of Cancer Preventiomentioning
confidence: 99%
“…The most common method to obtain the optimal tuning parameters λ and α is to use k-fold cross-validation. However, the results of selection are not stable due to that the samples are randomly split in the cross-validation (9). Meinshausen et al (18) proposed a stability selection method that used a half-sample approach in combination with selection algorithms.…”
Section: Statistical Models and Methodsmentioning
confidence: 99%
“…Due to the outperformance of the nPC (9) compared with the other PC-based dimension reduction techniques, PC and sPC, we only apply nPC to compare the performance with our proposed methods in real data analyses. We consider all genes according to the USCS (GRCh37/hg19) genome sequence annotation list which can be downloaded from the UCSC website (https://hgdownload.soe.ucsc.edu/goldenPath/hg19/bigZips/).…”
Section: Statistical Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations